REACTUALISATION AND RECONTEXTUALISATION OF CLASSICAL PESANTREN HERITAGE:: Efforts to Realise a Peaceful and Civilised Society - Mashar, Aly (ADP Publisher, 2025)
Pesantren have an extraordinary wealth of classical Islamic heritage. Many researchers have found that this classical Islamic heritage has become one of the factors enabling pesantren to maintain a polite and moderate religious understanding in Indonesian Muslim society, which has shifted in the opposite direction. Therefore, efforts to reactualise and expand the dissemination of polite Islamic values from pesantren to the broader community are needed. Furthermore, as society's character has changed due to the influence of modernity and technological developments, the methods and media used to disseminate these values must also be adapted to suit their character and conditions. This paper aims to answer these questions by examining the reactualisation of three stories from Sheikh Muhammad ibn Abu Bakar's al-Mawa'id al-'Usufiyyah. This research is library research using a linguistic analysis and interpretation approach. The interpretation, of course, is greatly influenced by the realities the researcher experiences. The primary sources of this research are Kitab al-Mawa'id al-'Usfuriyah and the researcher's experiences as a member of the Centre for the Study of Indonesian Society and Islamic Education (PPM-PIN) at UIN Surakarta since 2016. The results of this study show that: 1) The stories of Umar, Musa, and Bahrom, samples from the Kitab al-'Ushfuriyah, contain two central values that form the basis of polite behaviour in religion, namely: compassion and always thinking well of others. 2) Not all classical Islamic pesantren literature explains the values of religious politeness textually, but some require deep thought and reflection. 3) The appropriate dissemination media are those that utilise advances in information technology, such as Facebook, WhatsApp, TikTok, websites, YouTube, and so on. Additionally, dissemination can be done through pocketbooks, Friday leaflets, Friday sermon books, or other materials that can be directly given to individuals in the community.